Revealing the Competence of Multiprofessional Team Building among Students and Its Impact on the Effectiveness of Team Interaction - Olga V. Krezhevskikh; Adlet D. Kariyev (National Research Mordova State University, 2022)
Introduction. The need for a multiprofessional team is critical for the preschool stage where problems of individualization of education for children with disabilities and gifted children with behavioral deviations are solved. Despite the large number of publications on multiprofessional education, there are almost no researches into the readiness to multiprofessional interaction of preschool education specialists. The aim of the article is to present the results and methods for revealing the level of multiprofessional team building competence of students - future preschool education workers, to analyze the differences between the groups with high level of multiprofessional team building competence and the groups with low effectiveness of team interaction. Materials and Methods. Research sample: students of Shadrinsk State Pedagogical University (Russia) and Kazakh National Womenʼs Pedagogical University (Kazakhstan). Methods: expert observation (teachers competent in the fields of knowledge that students should operate in the research process were involved) using "field notes" and video recordings (qualitative and quantitative assessment according to the methodology of V.I. Zagvyazinsky, R. Atakhanov); questionnaires; interviews in focus groups; testing; expert evaluation of the effectiveness of team interaction; statistical criteria: Kolmogorova-Smirnova (single-sample) to determine the normality of distribution; Mann-Whitney U-criterion to identify the reliability of differences in groups with high levels of formation multiprofessional competencies from groups with low efficiency of team interaction. Results. It is proved that the formation of competence of multiprofessional team building is significant for the effectiveness of team interaction. The problems of multiprofessional interaction of preschool education workers are revealed: lack of willingness to conduct a dialogue with each other, weak or low degree of team-building and co-organizing activity, an attempt to associate the problem with the activity of one specialist, the desire to find the culprit in the situation. Discussion and Conclusion. The obtained results contribute to the development of the issue of readiness for interaction of specialists in defectological and non-defectological areas of training. In the future, it is advisable to investigate the issues of designing and evaluating the effectiveness of courses that develop the competencies of multiprofessional team building. The materials of the article can be useful in the developing standards of higher education of a new generation in terms of designing the planned learning outcomes of the academic programs and international recommendations on education.